Reading and writing invention and evolution: A learning model for beginning readers - Eny Kusumawati; Khairuddin Khairuddin (Proceedings of AICS - Social Sciences, 2013)
Reading and writing play important parts in human lives in this world both for adults and children, either in academic or non-academic setting. These literacy activities have brought about massive impacts on human cultural and biological nature. Because they are too fabricated in our lives, we tend to neglect how difficult are they for children to acquire in the first place, especially for children with certain dyslexic conditions. And because we merely take them for granted, few people, even language instructors or teachers, know how reading and writing systems were created and evolved, and how they are processed in the brain as opposed to verbal skills of listening and speaking, how first language and foreign language reading are differently processed and acquired in bilingual brain, how pictographic or sign-based writing system like the Chinese characters and syllabic or phoneme-based writing system like the Roman alphabets are (not) differently processed in our brain. Knowing how reading and writing were invented, evolved, and processed in the brain would tell us how to most effectively acquire these skills. This article employs a library research in the fields and literature of reading and writing system invention and evolution, and in neurolinguistics in order to satisfy the curiosity raised above. The article also suggests as the implication of their invention, evolution and neural process a model of literacy instruction that is based on phonics-reading approach as opposed to whole-word reading approach for both early first and second language reading instruction.Keyword: Literacy skills, neurolinguistics, bilingual brain, phonic-reading approach, whole-word reading approach, sign-based writing system, phoneme-based writing system